Islamic banking and finance in South-East Asia : its development and future - Venardos, Angelo M (Asia-Pacific business series, 2012)
"Islamic Banking and Finance in South-East Asia by Angelo M. Venardos has been a 'must read' since its first edition in 2005 and has already been translated to Arabic. Now in its 3rd edition, the book offers important updates you can look forward to, starting with the foundations of Islamic banking, developments and issues. The reader is then treated to a timely survey of Islamic banking in five South-East Asian countries. Most of these chapters have been completely revamped from the last edition. One additional chapter has been added on Islamic Succession Planning, which introduces an increasingly essential aspect of Muslim life--that of managing one's wealth now and in the afterlife. Whether you are new to the topic or a practitioner in the industry, you will appreciate the accessible way in which the book is written. According to the Asian Journal of Comparative Law, the book gives a broad overview yet 'manages to achieve this in a rather slim volume while providing depth of analysis at the same time'"--Provided by publisher